KEBUTUHAN INFORMASI INDIVIDU DOSEN DALAM PEMANFAATAN SUMBER INFORMASI DI PERPUSTAKAN PERGURUAN TINGGI - Rahmi, Lilatur; Husnah, Husna; Latifa, Maizi; Zulfitri; Zaindzikra, Dillah (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2024)
This study was designed to examine individual information needs in the utilization of library resources by lecturers asactive users in the Imam Bonjol State Islamic University Library Padang. The purpose of this study is to determine theinformation needs of lecturers with the availability of library materials and the extent to which these materials are usedby lecturers and provide recommendations for improvement. This research is a descriptive quantitative research with asample using proported stratified random sampling technique so that the number of samples is 193 people from 376lecturers as active users. The main finding of this study is that there are many library resources such as textbooks,journals, research monographs, research reports, newspapers, indexes/abstracts, internet services, as well asdictionaries/encyclopedias and others. Lecturers use the library mainly for consulting reference materials in the form ofperiodicals especially journal articles in electronic form at 65%. In general, 75% of lecturers need and use the library forresearch purposes and utilize books more than other sources of information. A number of recommendations weremade to improve library usage, but the most prominent suggestion was that the library should acquire more up-to-dateand relevant materials, and lecturers should be informed about newly acquired materials.